Bevacizumab for non-small cell lung cancer patients with brain metastasis: A meta-analysis - Liang Ping; Wang Yu-Dong; Wei Zong-Min; Deng Qi-Jun; Xu Tong; Liu Jiang; Luo Na; Hou Juan (Open Medicine, 2020)
This study evaluates the efficacy and safety of bevacizumab (BEV) in the treatment of non-small cell lung cancer (NSCLC) patients with brain metastases (BM) by performing meta-analyses of response and survival indices. Seventeen studies were included. BEV treatment was associated with a lower new BM incidence (hazard ratio: 0.30 [95% confidence interval (CI): 0.14, 0.46]) during follow-up. Disease control rate (DCR) of BEV-treated patients with BM was 91% [95% CI: 85, 95]. However, intracranial DCR was relatively higher (94% [95% CI: 87, 98]) than extracranial DCR (86% [95% CI: 74, 96]). DCR of NSCLC patients with BM was significantly better with BEV than with control therapies (odds ratio: 2.71 [95% CI: 1.26, 5.86], P = 0.01). Progression-free survival (PFS) of BEV-treated patients with and without BM was 7.1 months [95% CI: 6.2, 8.0] and 7.4 months [95% CI: 6.3, 8.4], respectively. Intracranial PFS of BEV-treated patients with BM was 8.0 months [95% CI: 6.0, 10.0]. Overall survival of BEV-treated NSCLC patients with and without BM was 13.5 months [95% CI: 11.4, 15.6] and 12.5 months [95% CI: 10.2, 14.8], respectively. The incidence of bleeding/hemorrhage in the central nervous system was 1% with BEV treatment.